[A plough] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
This is a plough which was used to prepare the land for sugar cane cultivation.
Cataloger's title
Keywords: Agricultural machinery -- Trinidad and Tobago; Caroni (1975) Limited